TAIJIQUAN AS PHYSICAL EDUCATION FOR STUDENTS - Petre BARBOȘ; Ioan-Nelu POP; Dumitru Rareş CIOCOI-POP; Dan Mihai GHERȚOIU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2019)
In recent years, with the opening of China's borders to the Western world, culture of this country have managed to attract millions of people. With a history of over 5,000 years, China has managed to amaze both through discoveries made, as by the martial arts, the most famous being the Shaolin School. Coming from Sholin schools, Taijiquan offered the chance to practice an accessible martial art as those with a superior physical training, as those who exercise a high intensity, has been banned for health reasons. Having in mind the numerous worldwide studies on Taijiquan. Faculty of Physical Education and Sport, Babeş-Bolyai University, Cluj, to implement a one-semester program (semester I, academic year, October 2018 -January 2019) of Taijiquan style, Yang short form (Long Box) (20 movements). The program included 46 students who did not practice sports. (23 students group witness and 23 students experimental group). Following this study one can say that Taijiquan exercises significantly improve balance and mental state (attention and memory).